Domicile - Andersson, Jerker 1966-; Andersson, Jerker 1966-; Molin, Johannes (Jerker Anderssons Förlag, 2019)
Pictures from one of many housing estates that sprang up in Sweden at a time when people increasingly moved into the country's expanding towns and cities in the early 1960s. Within the welfare state's vision of community and mass produced owner-occupied housing. Over the years, the exteriors have changed according to the owners' preferences, formed by a more individualistic society than when the houses were first built. The photos were taken in Falkenberg, Sweden, between 2006 and 2016 in the area where I lived during my first ten years, from 1966 to 1976